2001
DOI: 10.1159/000054199
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Renal Nerves and Endothelins in the Regulation of Renal Water Excretion in Diabetes insipidus Rats

Abstract: The interaction between renal nerves, endothelins acting via endothelin-A receptors and vasopressin in the regulation of renal excretory function was investigated. In conscious intact and renal denervated diabetes insipidus (DI) Brattleboro rats, as well as their controls, Long-Evans (LE) rats, an infusion of 16.4 nmol/kg/min ETA receptor antagonist BQ-123 was performed in the course of 50 min. Femoral artery blood pressure, heart rate, Ccr, V · UNa, V · UK and V · U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Intravenous treatment with the ET B receptor antagonist BQ-788, 25 nmol/kg.min at an infusion rate of 25 lL/min for 50 minutes, was performed in the fifth group of intact rats, six WKY rats and six spontaneously hypertensive rats, and in the sixth group of rats with BRD, six WKY rats and six spontaneously hypertensive rats. Doses of BQ-123 [11] and BQ-788 [12] used in the present study, were previously shown not to affect arterial blood pressure.…”
Section: Methodssupporting
confidence: 47%
“…Intravenous treatment with the ET B receptor antagonist BQ-788, 25 nmol/kg.min at an infusion rate of 25 lL/min for 50 minutes, was performed in the fifth group of intact rats, six WKY rats and six spontaneously hypertensive rats, and in the sixth group of rats with BRD, six WKY rats and six spontaneously hypertensive rats. Doses of BQ-123 [11] and BQ-788 [12] used in the present study, were previously shown not to affect arterial blood pressure.…”
Section: Methodssupporting
confidence: 47%
“…Continuous infusion of BQ‐123 and BQ‐788 was chosen to provide ET receptor blockade throughout the experimental period and the doses of BQ‐123 and BQ‐788 used in the present study were shown previously to effectively block renal ET receptors but to have no effect on systemic arterial BP (Matsuura et al. 1997, Girchev et al. 2001).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously observed that ET A receptor blockade with BQ‐123 had no effect on renal electrolyte excretion in Long–Evans (LE) (Girchev et al. 2001) but significantly reduced urinary sodium and potassium excretion in Wistar–Kyoto (WKY) rats (Girchev et al.…”
mentioning
confidence: 99%